Assistance and Legal Counseling in Agribusiness Cooperation Agreements Between Farmers and Bali Bali / PT. Suji Wood Leaves According to the Provisions of Article 1313 of KUHPERDATA - Diah Gayatri Sudibya; Kade Richa Mulyawati (Community Service Journal of Law, 2023)
Community Service as stated in the Higher Education Tri Dharma, is an activity that aims to help the community in several activities without expecting any kind of imbalance. In community service for the 2023 academic year, we from the UNWAR PKM Team provided assistance to young and old group farmers with Bulan Bali/PT Daun Kayu Suji in making a cooperation agreement. We are from UNWAR PKM Team, in carrying out this community service, found problems in business cooperation between farmers and Bulan Bali/ PT Daun Kayu Suji namely: 1. Parties do not understand the existence of a standard agreement as an agreement in business relations in accordance with the provisions of the law. 2. All this time the parties are in a business relationship, loyalty only relies on self-confidence and according to conscience. Based on the problems mentioned this PKM have some objective that are as a form of the Lecturer's dedication to the community, provide opportunities for lecturers to carry out direct service with partners to the target object, improving cooperative relations between universities and the community and/or companies that employ employees. The method that used in this PKM namely, directly meet partners to see directly the workplace situation at the Bali Moon company, discuss with the parties who will make a work agreement, the PKM implementation team can apply the methods used to carry out socialization and legal counseling regarding agreements.